Inequality and instability : a study of the world economy just before the Great Crisis - Galbraith, James K. (Oxford University Press, 2012)
As Wall Street rose to dominate the U.S. economy, income and pay inequalities in America came to dance to the tune of the credit cycle. As the reach of financial markets extended across the globe, interest rates, debt, and debt crises became the dominant forces driving the rise of economic inequality almost everywhere. Thus the "super-bubble" that investor George Soros identified in rich countries for the two decades after 1980 was a super-crisis for the 99 percent-not just in the U.S. but the entire world. Inequality and Instability demonstrates that finance is the driveshaft that li.